Utilization of sargassum based activated carbon as a potential waste derived catalyst for low temperature selective catalytic reduction of nitric oxides. (15th November 2015) - Li, Wei; Tan, Shan; Shi, Yun; Li, Sujing
Highlights: N-doped sargassum based activated carbon is prepared via different techniques. NOx conversion of commercial AC is 50.84%. C/SAC-2/U-6 achieved a maximum NOx conversion of 87% at 150 °C. The characterization of catalysts was determined by EA, BET, XPS and FTIR. C/SAC-2/U-6 has an excellent water-tolerance and sulfur-tolerance. Abstract: The use of activated carbon derived from sargassum (SAC), normally disposed as waste, has been examined as potential catalyst for selective catalytic reduction of NO with NH3 (NH3 -SCR) in the temperature range of 50–250 °C. The influence of important process variables, such as preparation methods, phosphoric acid impregnation ratios and surface nitrogen functional groups, were investigated. The impacts of water (H2 O) and sulfur dioxide (SO2 ) on the SCR activity of the C/SAC-2/U-6 catalyst were also discussed. An array of analytical techniques, including Brunauer–Emmett–Teller method (BET), Elemental Analysis (EA), Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS) were also employed to study the structural properties, elemental content, and distribution of nitrogen-containing groups of the catalyst prepared. Experimental results suggested that the urea modified C/SAC-2/U-6 sample exhibited higher NOx conversion, better N2 selectivity and broader operation temperature window than all the SAC samples and the commercial activated carbon sample. Moreover, it has good water and sulfur tolerance, making the sargassum derived catalyst as a promising NH3 -SCR catalyst for NOx emission from fired power plant.